Shape Memory Alloy connectors for Ultra High Vacuum applications: a breakthrough for accelerator technologies - Niccoli, Fabrizio; Furgiuele, Franco; Cedric, Garion (My University, 2017)
The design of tight connections for ultrahigh-vacuum (UHV) systems is a key subject for vacuum technology. Design requirements become even more stringent when dealing with UHV beam-pipe coupling in high-energy particle accelerators, where reliability and safety are core issues. For this specific application, additional needs often arise: strict geometrical and/or space limitations, connection of dissimilar materials and installation in restricted access areas. The latter constraint is of major concern, especially in the new generation of high-energy particle accelerators such as the HL-LHC (High Luminosity Large Hadron Collider), which will be operational at CERN (European Organization for Nuclear Research) in 2026. Owing to the increased proton-beam intensity and luminosity of the HL-LHC, radioactivity will be higher at some points than in the present LHC. The radiation exposure time of the technical personnel in some critical areas will be strictly controlled and minimized. The use of standard ConFlat® flanges (CF) or quick connect ConFlat® flanges (QCF) could result in significant design and operational/maintenance limitations. In particular, the mounting and dismounting of CFs are time-consuming due to the high number of bolts and lead to significant radiation doses incurred by operators. Conversely, QCFs can be installed more quickly, but they suffer from the requirement of more space and are unwieldy components comprising heavy stainless-steel chain clamps. Within this framework, Shape Memory Alloys (SMAs) offer a unique possibility to generate tight connections and fast clamping/unclamping by remotely changing the temperature of the SMA junction unit; at the microscopic scale this occurs trough a reversible solid-state transformation between the parent austenitic phase and the product martensitic one. In this PhD work, SMAs were used to develop a new generation of vacuum tightening systems for accelerator beam-pipe coupling by exploiting their shape recovery capabilities and actuation principles. The proposed coupling system consists of a SMA ring and a sealing element to be placed at the SMA-vacuum chambers interface, i.e. a copper coating or a thin cylindrical aluminum/copper gasket. Commercial NiTiNb rings and NiTi sleeves ad-hoc developed by Intrinsic Devices Inc. (USA) based on CERN technical constraints were properly investigated. The rings show two-way shape memory effect 􀍞remembering􀍟 a contracted austenitic shape and an enlarged martensitic one. The thermomechanical properties of the selected SMAs were measured experimentally. The tightening performance of SMA rings, was studied for different values of the initial clearance between the SMA ring and the vacuum pipe. The contact pressure was estimated by both strain gauge (SG) measurements and by Digital Image Correlation (DIC), using an ad-hoc developed numeric procedure. A novel design method was proposed that involves numerical results, obtained from Finite Element (FE) simulations and a literature vacuum sealing model. Leak tightness tests were carried out to assess the sealing performance of the of SMA-based prototype UHV chambers even after ageing at room temperature and repeated thermal cycles. Irradiation tests on SMA-based prototype vacuum chambers (SMA absorbed dose > 100 kGy) was performed at CHARM (Cern High energy AcceleRator Mixed field) facility at CERN and the functional and leak tightness performance of the couplings was successfully verified afterwards. The main results revealed that the contact pressure is not significantly affected by the initial SMA ring-pipe assembly clearance due to the plateau in the stress-strain response of the material. Thermal dismounting and subsequent re-clamping is obtained by exploiting the two-way shape memory recovery capabilities of the alloys. Leak rate measurements showed that the constraints for UHV applications could be easily satisfied (leak rate < 10-10 mbar l s-1) even after multiple thermal cycles; this opens the possibility of remotely clamping/unclamping the tight couplers by well-defined temperature variations. The proposed SMA-based beam-pipe couplers can be installed without using any connection flange. They are smaller and lighter than CF and QCF devices currently used in UHV systems at CERN. These bolt-free SMA-based connectors could provide significant benefits in terms of installation-dismounting time, space occupancy, bi-material joining and, above all, possible remote thermal activation, obtainable, for example, with removable heating/cooling collars. Based on these results, possible applications in CERN accelerators have already been identified. A first use has been proposed for the ISOLDE (Isotope Separator On Line DEvice). A second application is the vacuum system of the Large Hadron Collider (LHC) between the two high-luminosity experiments (ATLAS and CMS) and the beam focusing-defocusing quadrupole magnets (frequently called inner triplets). Moreover, particle collimators are also critical devices of accelerator equipment. In all these applications, high-energy particles induce a large radioactivity and, consequently, personnel access is restricted. The use of SMA rings with remote clampingunclamping features could be beneficial to avoid contamination and irradiation of technical personnel. Finally, SMA coupling installations are already planned in the CLEAR test facility at CERN, which provides the electron beam for the Compact Linear Collider (CLIC) study.
Dottorato di Ricerca in Ingegneria Civile e Industriale. Ciclo XXIX
Keywords: Shape memory alloys; Vacuum technology